Mobile Technologies for Delivering Healthcare in Remote, Rural or Developing Regions - Ray, Pradeep Kumar; Nakashima, Naoki; Ahmed, Ashir; Soshino, Yasuhiro; Chul,RoSoong- (Stevenage : The Institution of Engineering and Technology, 2020)
This edited book explores the use of mobile technologies such as phones, drones, robots, Apps, and wearable monitoring devices for improving access to healthcare for socially disadvantaged populations in remote, rural or developing regions
Keywords: Medical Informatics Applications; medical health innovation; mobile health applications